ASSESSMENT OF THE IMPACT OF FUEL SUBSIDY REMOVAL ON IRRIGATION-BASED RICE PRODUCTION IN NORTH-EASTERN STATE, NIGERIA - Hamidu, B.; Sale, I.; Usman, A. B.; Daiyabu, M. L.; Musa, A. U. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study examined the impact of fuel subsidy removal on irrigation-based rice production in Bauchi and Gombe States, Nigeria. A multistage sampling procedure was used to select seven hundred and seventeen farmers in the study area. Data were collected through the use of structured questionnaire. The data were analyzed using descriptive statistics and budgeting model. The results revealed that almost all (92.19%) of the respondents in Bauchi and Gombe State were male with majority (68.90%) of them being married. The result also revealed the mean household size, mean farm size, farming experience and mean monthly income of; 9 persons per household for both States, 3ha, 9 years for Bauchi and 15 years for Gombe, N115,355.43 for Bauchi and N 70,454.36 for Gombe respectively. The result of the budgeting model revealed the mean total cost, mean total revenue, mean gross margin, mean net income and return per Naira invested before the removal of fuel subsidy in Bauchi State as N 227,965.623, N 1,735,630.3, N 1,552,610.6, N 1,507,664.7 and N 8.48 respectively. While after the removal of fuel subsidy the mean total cost, mean total revenue, mean gross margin, mean net income and return per Naira invested in Bauchi State was found as N 342,032.523, N 2,442,184.8, N 2,166,717.2, N 2,100,152.3 and N 7.8 respectively. The result also revealed the mean total cost, mean total revenue, mean gross margin, mean net income and return per Naira invested before the removal of fuel subsidy in Gombe State as N 177,716.51, N 1,800,000, N 1,667,229.43, N 1,622,283.49 and N 12.55 respectively. The result of the findings further indicated that majority (70.20%, 68.55%, 64.89% and 66.43%) of respondents in Bauchi and Gombe States strongly agreed that subsidy removal had negatively affected their livelihood by bringing about high cost of transportation and increase in the price of basic food stuff. The study concluded that irrigated rice farming was profitable before and after the removal of the fuel subsidy in Bauchi and Gombe States. However, it was discovered that the constraints to irrigated rice farming in the two States were high cost of fertilizer, high fuel cost and low price of paddy rice. It was therefore recommended that, alternative irrigation systems such as solar powered irrigation systems should be encouraged, provision of adequate palliative measures, providing subsidy to farmers particularly on fertilizer and other inputs by the federal /State Government as well as discouraging the importation of rice into the country to encourage local production.